A rare case of facial asymmetry caused by simultaneous development of osteochondroma and synovial chondromatosis at the temporomandibular joint. Issue 2 (March 2023) - Kaneko, Ichiro; Karino, Masaaki; Osako - Sonoyama, Rie; Ishizuka, Shinji; Toda, Erina; Kanayama, Junichi; Okuma, Satoe; Tatsumi, Hiroto; Okui, Tatsuo; Kanno, Takahiro
Abstract: Osteochondromas (OCs) are rare benign tumors of the temporomandibular joint (TMJ) area, while synovial chondoromatoses are rare benign tumor-like disease. Few reports on the simultaneous development of an OC and synovial chondromatosis have been published. We describe here an extremely rare case of facial asymmetry caused by an ipsilateral OC and synovial chondromatosis at the TMJ. A patient was referred to our department with a chief complaint of malocclusion. Cephalometric photographs showed facial morphological asymmetry, and computed tomography imaging revealed a left condylar head tumor and multiple calcified lesions in the superior joint space. A dentofacial deformity induced by a tumor at the left condylar head and synovial osteochondromatosis at the left TMJ was diagnosed. He initially underwent condylectomy and tumorectomy. Histopathologically, the mandibular surface was elevated and capped with cartilage that exhibited weak atypia and a low cell density. The bone beneath the cartilage cap was thickened, but no atypia was noted. In the second surgical step, bilateral sagittal split ramus osteotomy was performed to improve the facial appearance and achieve normal occlusion. Finally, three dental implants were inserted to replace missing teeth for oral rehabilitation. Three years have passed since the completion of all treatments, and the patient is progressing well without recurrence of the TMJ tumor or mandibular deviation. Mandibular movement is normal, and the final occlusion and facial appearance remain satisfactory.